2015
DOI: 10.1002/jms.3563
|View full text |Cite
|
Sign up to set email alerts
|

A UPLC-MS/MS method for simultaneous quantitation of three monoterpene glycosides and four alkaloids in rat plasma: application to a comparative pharmacokinetic study of Huo Luo Xiao Ling Dan and single herb extract

Abstract: The objective of this study was to develop a sensitive and reliable ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for simultaneous quantitation of three monoterpene glycosides (paeoniflorin, alibiflorin and oxypaeoniflorin) and four alkaloids (tetrahydropalmatine, corydaline, dehydrocorydaline and berberine), the main active ingredients of Radix Paeoniae Rubra extract (RPE) and Corydalis yanhusuo extract (CYE) in Huo Luo Xiao Ling Dan (HLXLD), and to compare the pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…These data indicated that some ingredients in HLXLD might reduce the bioavailability of phthalides and slow down the elimination processes of five phthalides in rats. HLXLD is a decoction of 11 herbs; each of them could produce specified pharmacological effects, and might have different influences on the absorption and metabolism of the five different components . It has already been published that the absorption of the phthalide compounds was inhibited after DG‐CX and Paeonia lactiflora Pall decocted together in another Chinese formula Danggui–Shaoyao–San .…”
Section: Resultsmentioning
confidence: 99%
“…These data indicated that some ingredients in HLXLD might reduce the bioavailability of phthalides and slow down the elimination processes of five phthalides in rats. HLXLD is a decoction of 11 herbs; each of them could produce specified pharmacological effects, and might have different influences on the absorption and metabolism of the five different components . It has already been published that the absorption of the phthalide compounds was inhibited after DG‐CX and Paeonia lactiflora Pall decocted together in another Chinese formula Danggui–Shaoyao–San .…”
Section: Resultsmentioning
confidence: 99%
“…We tried columns with different lengths and diameters such as the BEH C 18 (2.1 × 50 mm, 1.7 μm) and BEH C 18 (2.1 × 100 mm, 1.7 μm) and found that the peak time and the peak effect of the former were the best (Ai et al, 2015;Cai et al, 2016;Dong, Yu, Deng, & Pan, 2016). The BEH C 18 column, a universal one for UPLC separations, was selected in this study for the trifunctionally bonded BEH particle with superior low pH stability and ultra-low column bleed over the pH range 1-12.…”
Section: Methods Optimizationmentioning
confidence: 99%
“…The BEH C 18 column uses Waters proprietary technology for end-cap packing to ensure the peak shape of basic compounds, providing sharply symmetric peaks for highest efficiency and UPLC-MS/MS detection sensitivity. We tried columns with different lengths and diameters such as the BEH C 18 (2.1 × 50 mm, 1.7 μm) and BEH C 18 (2.1 × 100 mm, 1.7 μm) and found that the peak time and the peak effect of the former were the best (Ai et al, 2015;Cai et al, 2016;Dong, Yu, Deng, & Pan, 2016). Alkaloids on the column were prone to peak tailing.…”
Section: Methods Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu (12 g), Gentiana macrophylla Pall (12 g), Cinnamomum cassia Presl (15 g) and Glycyrrhiza uralensis Fisch (12 g) (Lao et al, 2006). Previous studies from our laboratory had been carried out on the pharmacokinetic profiles of several components in HLXLD (Wang et al, 2014;Wu et al, 2015aWu et al, , 2015bAi et al, 2015aAi et al, , 2015b, but Salvia miltiorrhiza (SM) as the sovereign drug ('Jun') in this recipe, which has effect on promoting blood circulation, alleviating pain and targeting illness, was not studied. Tanshinones (particularly tanshinone I, tanshinone IIA, tanshinone IIB, dihydrotanshinone I and cryptotanshinone) are considered as the main bioactive compounds of S. miltiorrhiza, responsible for its anti-inflammatory, analgesic effect and inhibitory effects on 5-lipoxygenase and cyclooxygenase Kim et al, 2002;Cao et al, 2010).…”
Section: Introductionmentioning
confidence: 98%